Ovarian metastasis of malignant melanoma: The first pediatric case - Yuko Araki; Hide Kaneda; Kohei Oashi; Sathoshi Okada; Arata Tsutsumida (Elsevier, 2014)
We report a case of an 8-year-old girl with metastasis of malignant melanoma (MM) to the ovary. She was initially diagnosed with cutaneous MM on the left buttock for which she underwent wide local excision, left inguinal/pelvic lymph node dissection, and subcutaneous injection of interferon beta. In spite of the treatment, she developed dissemination of MM to the liver, the bone, and the right ovary. All the lesions responded well to systemic chemotherapy (intravenous dacarbazine), except for the right ovarian tumor. She underwent an elective right salpingo-oophorectomy to avoid torsion or rupture of the tumor. However, she developed metastases to the contralateral ovary with peritoneal dissemination in 4 months. She received home palliative care and died at home 14 months after the last surgery. Ovarian metastasis of MM is a rare form of dissemination, and only 15 adult cases have ever been reported. Our patient is the first pediatric case. Since there is no standard of surgical indication for metastatic MM to the ovary, palliative resection can be an option for improving quality of life of a patient with this rare condition.